LncRNA‐FENDRR mediates VEGFA to promote the apoptosis of brain microvascular endothelial cells via regulating miR‐126 in mice with hypertensive intracerebral hemorrhage. (10th October 2018) - Dong, Baizhuo; Zhou, Bin; Sun, Zhigang; Huang, Shengming; Han, Liang; Nie, Honghua; Chen, Guohui; Liu, Shibing; Zhang, Yanna; Bao, Ning; Yang, Xiaolong; Feng, Hongwei
Abstract: Background: LncRNA‐FENDRR is a kind of endothelial genes critical for vascular development. Moreover, miR‐126 and vascular endothelial growth factor A (VEGFA) are also involved in the physiological process of vascular endothelial cells. This study aimed to the underlying mechanism of FENDRR involving miR‐126 and VEGFA in hypertensive intracerebral hemorrhage (HICH). Methods: C57BL/6 mice were chosen to establish HICH model. The expression of FENDRR, miR‐126, and VEGFA at mRNA level was determined by qRT‐PCR. The protein expression of VEGFA was assessed using Western blot. RIP assay and RNA pull‐down assay were used to the relationship between FENDRR and miR‐126. Flow cytometry was used to analyze cell apoptosis. Results: The levels of FENDRR and VEGFA were increased, and miR‐126 expression was decreased in vascular endothelial cells (VECs) from the right brain of model mice and human brain microvascular endothelial cells (HBMECs) treated by thrombin. Overexpression of FENDRR promoted the apoptosis of HBMECs. FENDRR regulating VEGFA participated in HBMECs apoptosis through targeting miR‐126. Downregulation of FENDRR was indicated to relieve the HICH in mice. Conclusions: FENDRR could promote the apoptosis of HBMECs via miR‐126 regulating VEGFA in HICH.